Ответы 2

  • огромное спасибо
  •  {(x + 2)}^{3}  +  {3x }^{2}  - 11 =  {(x + 3)}^{3}  \\  {x}^{3}  \times  {6x}^{2}  + 12x + 8 +  { 3x}^{2}  - 11 =  \\  {x}^{3}  +  {9x}^{2}  + 27x + 27 \\  {9x}^{2}  + 12x - 3 =  {9x}^{2}  + 27x + 27 \\ 12x - 3 = 27x + 27 \\ 12x - 27x = 27 + 3 \\  - 15x = 30 \\ x = 30 \div ( - 15) \\ x =  - 2
    answer img
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years